Effect of Cob Bone–Derived Hydroxyapatite as a Reinforcing Material for Heat-Cured Acrylic Resin Denture Base: Hydroxyapatite for Denture Base Strengthening - Syafrinani Syafrinani; Veronica Angelia; Yunita Dea Mikha Gultom (Journal of Syiah Kuala Dentistry Society, 2025)
Heat-cured acrylic resin breaks easily when bumped suddenly, but this can be prevented by adding hydroxyapatite from cob bones. The purpose of this research was to determine the effect of the addition of cob bone hydroxyapatite from 3%, 4%, and 5% as a reinforcing material for heat-cured acrylic resin denture bases on impact strength. The samples were added by reinforcing material in the form of hydroxyapatite powder at 3%, 4%, and 5% of the polymer weight in a mold measuring 80 x 10 x 4 mm with 12 samples in each group, then cured at 70° C for 90 minutes and increased at 100° C for 30 minutes. The impact strength of the acrylic resin was measured using a Charpy Impact Tester. The samples were tested using univariate analysis with the results of the mean impact strength in the control group 10.77±1.53 x 10-3 J/mm2, the group after the addition of 3% hydroxyapatite 9.60±1.47 x 10-3 J/mm2, the group after the addition of 4% hydroxyapatite 8.35±1.47 x 10-3 J/mm2, the group after the addition of 5% hydroxyapatite 7,01±0,90 x 10-3 J/mm2. Data were analyzed using one-way ANOVA and LSD (Least Significant Difference). Adding hydroxyapatite powder had a significant effect (p = 0.001; p < 0.05). The highest impact strength of heat-cured acrylic resin was observed in the control group, followed by 3% and 4% hydroxyapatite additions, and finally 5%.